The Influence of Reading and Writing Literacy in Introducing Islamic Values in Early Childhood at TK Putra II Serang - Nurasiah, Siti; Imamah (Kirana Publisher (KNPub), 2024)
This study aims to analyze the effect of reading and writing literacy on the understanding and acceptance of Islamic values in early childhood at Putra II Kindergarten, Serang District. Using associative method and quantitative approach, this study examines the relationship between the independent variable, namely reading and writing literacy, and the dependent variable, namely understanding and acceptance of Islamic values. This study used SPSS version 24 software to analyze numerical data obtained from questionnaires and observations. The research subjects were early childhood children with an age range of 4 to 6 years old with a total of 54 children. This research is required to make an important contribution to the development of more effective Islamic religious education methods at the early childhood education level. The hypothesis tested is that there is a positive and significant influence between reading and writing literacy and understanding of Islamic values in early childhood. The research was conducted at TK Putra II Serang from May to June 2024. The limited time for data collection and analysis may have affected the findings. This research will also analyze the long-term impact of implementing learning that integrates literacy and Islamic values in early childhood. Thus, this study can provide empirical evidence on the benefits and effectiveness of this approach in preparing children to have good literacy skills and a strong understanding and appreciation of religious values. The results showed that the value of r is smaller than the level a used which is 0.000 or 0.000 <0.05 so that Ho is rejected and Ha is accepted, which means that there is a significant effect of reading and writing skills on Islamic values at Putra II Serang Kindergarten